STUDY ON THE INTEGRITY OF GAS AND CRUDE OIL PIPELINE DUE TO EXCESSIVE LATERAL DEFLECTION - DAHLAN MANURUNG (NIM : 13106139); Pembimbing : Prof.Dr. Indra Nurhadi, TEDDY
Pipeline as an artery of transportation for oil and natural gas plays a very important role in oil & gas industry. Pipeline needs to be maintained to avoid failure that will cause the decline in production. Any disruption in the pipeline should be anticipated at an early stage to take action in the repair of pipe. Moreover , to know of repaired pipe is also important to know whether repair works are beneficial to the pipe. In this final project, pipline in Kondur Petroleum S.A. experienced some form of disturbance, they are buckling in pipeline along 708 m and 0.5 m high from the soil, pipe that experienced extreme deformation even pipe has shrinkaged so action to patch pipe was taken, and pipeline that deformed excessively caused by fallen tree. For the three of these case, we want to know stess that occured in pipes due to disruption experienced by the pipe, and also know the maximum height for buckling pipe from the soil so that fail not occur for the first case. The result of stress analysis using Palmer method for buckling pipe in the first case shows the stess that occurs in pipes is 101.961 Mpa. The value of this stress is still below SMYS (Specified Yield Minimum Strength) of pipe (241.35 Mpa). While the maximum heigth of buckled pipe so that pipe not fail using coloum buckling teori is 0.5735 m from soil. For the second case stress analysis with linear analysis using ANSYS 12.1 for the pipe before patched, shows the maximum von Mises stress very large compare to the pipeÃ‚Â’s UTS (Ultimate Tensile Strength, 414 MPa) so the analysis must be continued to non linear analysis. The result for non linear analysis of this pipe after patching shows the maximun von Mises stress is about 114 MPa. This value is still below the SMYS of pipe (241 MPa) showing there is an improvement on the pipe after patching. For the third case, stress analysis of the pipe fallen off by tree, the maximum von Mises stress with non linear analysis using ANSYS 12.1 on pipe is about 294 MPa. This value is still below the SMYS of pipa (241 MPa) showing the pipe has fail.